Lighting and Air Temperature Monitoring and Control of Hydroponic System using Internet of Things (IoT) - Khairulnizam; Basharie, Siti Mariam; Othman, Khairulnizam; Raman, Thayaaniti (Multidisciplinary Applied Research and Innovation, 2020)
The efficiency of plant’s growth rate depends heavily on the environmental factors. Parameters such as temperature, humidity, lighting quality, pH, and nutrients should be provided to a plant in sufficient amount. If one of these parameters below than the ideal growth limit, it will impact the growth of the plant. As a results, farmers need to give more attention for their plants to produce a healthy plant. Other than that, it will increase their workload because they have to interact with plant all the time and their daily activities will be affected. Besides that, insufficient information or data about the plants will also lead to ineffective production of crops. To overcome these problems, one of the solutions is to use Internet of things (IoT) in their growth method. This study is intended to design a monitoring and control system for the hydroponic application. Parameters such as surrounding humidity, lighting quality and temperature was controlled using NodeMCU microcontroller unit with the help of an internet connection. Sprinkler system and growth lights were used to control and provided the plant with sufficient amount of temperature and lights. ThingSpeak cloud application was used to gather and store data in cloud storage whereas, Blynk application was used to monitor and control the system. To identify the difference between the growth rate of controlled parameter and uncontrolled parameter system, another system without the controlled parameters has been setup. The system which developed in this project will reduce the workload of the farmers. The farmers can monitor and control their plants from wherever there are or on the go. All the temperature and humidity data were stored in the cloud storage for the future usage. It is shown that the growth rate of Chinese kale plant has increased consistently using system with controlled environment compared to system without any parameter controlled.